Research methods in human skeletal biology - DiGangi, Elizabeth A.; Moore, Megan K. (Amsterdam Academic Press, 2013)
Research Methods in Human Skeletal Biology serves as the one location readers can go to not only learn how to conduct research in general, but how research is specifically conducted within human skeletal biology. It outlines the current types of research being conducted within each sub-specialty of skeletal biology, and gives the reader the tools to set up a research project in skeletal biology. It also suggests several ideas for potential projects. Each chapter has an inclusive bibliography, which can serve as a good jumpstart for project references. Provides a step-by-step guide to conducting research in human skeletal biology. Covers diverse topics (sexing, aging, stature and ancestry estimation) and new technologies (histology, medical imaging, and geometric morphometrics). Excellent accompaniment to existing forensic anthropology or osteology works.
Introduction to skeletal biology -- Application of the scientific method to skeletal biology -- Age-at-death estimation -- Sex estimation and assessment -- Ancestry estimation -- Stature estimation -- Paleopathology -- Investigation of skeletal trauma -- Taphonomy -- Dental anthropology -- Demography -- Geometric morphometrics -- Bone and dental histology -- Functional morphology and medical imaging -- Isotopes -- Molecular methods -- Library research, presenting, and publishing -- Future research considerations in human skeletal biology.
Keywords: Forensic anthropology -- Textbooks; Human skeleton -- Research -- Methodology